Effectiveness of Primary School Co-Curricular Activities in Instilling Democratic Values Among Pupils in Public Primary Schools in Igembe South Sub-County - A Critique Based on John Rawls Theory of Justice - Kailikia, Priscilla Mwonjiru; Kamoyo, John Mwithalii; Ogola, Fredrick (European Scientific Journal, ESJ, 2024)
This study focused on the effectiveness of primary school co-curricular activities in instilling democratic values among pupils in public primary schools in Igembe south sub-county. A critique based on John Rawls theory of justice. The study adopted descriptive survey research design. The target population was 6700 comprising of 5950 standard seven pupils and 750 teachers in public primary schools in Igembe South Sub-County. Simple random sampling was used to select 325 pupils while purposive sampling was used to select 45 teachers forming a total sample of 370 respondents. Data was collected using questionnaires. Collected data was cleaned, coded and entered in the computer for analysis using SPSS version 23. The study used Quantitative and qualitative data. Quantitative data was analyzed using frequencies and percentages. Qualitative data was analyzed thematically. The findings of the study revealed that Primary school co-curriculum activities were found relevant in instilling democratic value of socio-economic equality highlighted in the John Rawls theory of justice. The study further revealed that co-curricular activities promoted democratic value of equal liberty among pupils because they inculcate culture of sharing. Based on this, the study recommended that, head teachers ought to emphasize on the importance of pupils’ participation in co-curriculum activities in the process of curriculum implementation and supervision. This is because the study has exposed that co-curriculum activities are significant in enhancing democratic values.